1998
DOI: 10.1046/j.1365-2362.1998.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor β alleles and hyperinsulinaemia in coronary artery disease

Abstract: This study demonstrates an association of TNF-beta alleles with the risk factor hyperinsulinaemia in CAD. Genomic variants of TNF-beta may therefore contribute to the complex susceptibility for the metabolic syndrome in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…The risk was explained partially by systemic inflammatory markers, such as IL-6, CRP, fibrinogen, and P-selectin. Our results also are consistent with another Japanese case-control study (5) and a trio family study of 460 families recruited from the United Kingdom, Sweden, Germany, and Italy (6) but not with three casecontrol studies in white individual, in which no association was found (7)(8)(9). This difference may be related to the smaller Figure 3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The risk was explained partially by systemic inflammatory markers, such as IL-6, CRP, fibrinogen, and P-selectin. Our results also are consistent with another Japanese case-control study (5) and a trio family study of 460 families recruited from the United Kingdom, Sweden, Germany, and Italy (6) but not with three casecontrol studies in white individual, in which no association was found (7)(8)(9). This difference may be related to the smaller Figure 3.…”
Section: Discussionsupporting
confidence: 91%
“…In following up on significant findings, 10 common single-nucleotide polymorphisms (SNP) of the LTA gene were studied, and 252A/G in intron 1 was found to be almost completely linked to a missense mutant (Thr26Asn) in exon 3 and associated with MI; subsequent functional assays showed a higher transcriptional activity associated with the 252G allele and higher mRNA expression of vascular cell-adhesion molecule 1 and E-selectin associated with the 26Asn allele. The association of the 252G allele or 26Asn allele with coronary artery disease or MI was confirmed in another Japanese casecontrol study (5) and a trio family study of white individuals (6) but not in three other case-control studies in white individuals (7)(8)(9). Because most of those studies were retrospective, the selection of case patients and control subjects could bias the association, and prospective studies are warranted.…”
mentioning
confidence: 99%
“…No association was found with the presence or extent of coronary disease or with previous infarction although, in the patient group, heterozygosity for Thr 26 was associated with hyperinsulinaemia. 18 Another variant (A252G in intron 2), which correlates with increased TNF β concentrations, was also not associated with myocardial infarction. 5 Thus, the TNF polymorphisms explored so far do not appear to be linked to IHD.…”
Section: Tnf α Polymorphismsmentioning
confidence: 96%
“…Type 2 diabetes mellitus (DM) is associated with increased oxidative stress [1], endothelial dysfunction [2][3][4][5][6] and increased levels of pro-inflammatory cytokines such as interleukin-6 (IL-6) [7][8][9][10] and tumour necrosis factor alpha (TNF-α) [7,[11][12][13]. These cytokines may stimulate the expression of adhesion molecules on endothelial cells [e.g.…”
Section: Introductionmentioning
confidence: 99%